2016
DOI: 10.1089/cyber.2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Primary School Children's Knowledge of Online Safety and Risks with the CATZ Cooperative Cross-Age Teaching Intervention: Results from a Pilot Study

Abstract: Children are heavy users of the Internet and prior studies have shown that many of them lack a good understanding of the risks of doing so and how to avoid them. This study examined if the cross-age teaching zone (CATZ) intervention could help children acquire important knowledge of online risks and safety. It allowed older students to act as CATZ tutors to design and deliver a lesson to younger schoolmates (tutees), using content material about online risks and safety provided by adults. Students in Year 6 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, future research should explore whether these attitudes translate into their actual behaviour when acting as a positive bystander for both forms of bullying. A previous study showed that such beliefs may be engendered effectively by allowing older students to teach their younger peers about such matters (Boulton et al 2016). This, in turn, may promote and encourage future PBRs across all pupils.…”
Section: Discussionmentioning
confidence: 99%
“…However, future research should explore whether these attitudes translate into their actual behaviour when acting as a positive bystander for both forms of bullying. A previous study showed that such beliefs may be engendered effectively by allowing older students to teach their younger peers about such matters (Boulton et al 2016). This, in turn, may promote and encourage future PBRs across all pupils.…”
Section: Discussionmentioning
confidence: 99%
“…Following data collection, researchers initially read through the responses and arrived at a coding scheme of the most common responses for online dangers/safety. The coding frame was then reviewed and revised to meet prior research recommendations on children's online risks and how to stay safe online (Boulton et al, 2016;Chaudron et al, 2015;Livingstone et al, 2011). To receive an expert opinion, the coding frame was assessed by one of the authors who had prior experience in the police force being responsible for promoting e-safety issues and who is now currently responsible for child protection and advising safeguarding boards/committees.…”
Section: Methodsmentioning
confidence: 99%
“…Inter-coder reliability was high, 93%. This method is recognised as an accurate measurement (Gwet, 2014), and the use of a coding system has been used in prior research to establish an 'overall' score for the desired variable (Boulton et al, 2016;Macaulay, Boulton, & Betts, 2018;Saldaña, 2015). Krippendorff's alpha (α) was calculated to assess the reliability of the overall coding scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Co-operative group work (CGW) has been shown to assist students' learning in academic (Baines et al, 2007;Veldman et al, 2020) and social/behavioural domains (Blatchford et al, 2006;Cowie et al, 1994), including anti-bullying learning (Boulton et al, 2016;Ttofi & Farrington, 2011). Similarly, cross-age teaching (CAT) approaches have been shown to benefit tutors' academic development (Karcher, 2009;McDaniel & Besnoy, 2019;Robinson et al, 2005;Topping et al, 2011) and social/behavioural development (Robinson et al, 2005;Watts et al, 2019).…”
Section: The Cross-age Teaching Zone Interventionmentioning
confidence: 99%